Laboratory investigation of lunar surface electric potentials in magnetic anomaly regions. Issue 11 (2nd June 2015) - Howes, C. T.; Wang, X.; Deca, J.; Horányi, M.
Abstract: To gain insight into lunar surface charging in the magnetic anomaly regions, we present the results of laboratory experiments with a flowing plasma engulfing a magnetic dipole field above an insulating surface. When the dipole moment is perpendicular to the surface, large positive potentials (close to ion flow energies in eV) are measured on the surface in the dipole lobe regions, charged by the unmagnetized ions while the electrons are magnetically excluded. The potential decreases exponentially with distance from the surface on the ion (flow) Debye length scale. The surface potentials become much smaller when the dipole moment is parallel to the surface, likely due to collisionality. We discuss the implications of our laboratory results for the lunar surface charging in the magnetic anomaly regions, suggesting that the surface potential may be much higher than the generally expected several volts positive due to photoemission. Key Points: Positive surface potentials are measured within magnetic dipole fields Potentials decrease with distance from surface on the ion Debye length scale Large positive potentials may form on lunar surface in magnetic anomaly regions